High CMRR Wide Bandwidth Instrumentation Amplifier Based on VDBA - Gupta, Priyanka; Pandey, Neeta; Pandey, Rajeshwari (Recent Advances in Electrical & Electronic Engineering, 2018)
Background: In this paper, a novel instrumentation amplifier (IA) based on voltage differencing buffered amplifier (VDBA) is presented. The proposed IA consists of a single VDBA and a resistor and offers high common-mode rejection ratio (CMRR). The effects of non-idealities of the VDBA are analyzed and the corresponding mathematical formulation is derived. Methods: Theoretical analysis of the proposed circuit is verified through SPICE simulation using 180nm technology process parameters. Both frequency and transient responses are shown. Output and input noise densities are formulated for the proposed circuit and verified through the simulation results. Results: A CMRR magnitude of 198 dB with 3dB bandwidth of 2.81MHz is obtained for the proposed configuration. Conclusion: To investigate the effect of mismatches on the CMRR performance of the proposed circuit, Monte Carlo statistical analysis is also performed.
Keywords: CMIA